Effects of Iron and Zinc on Mitochondria: Potential Mechanisms of Glaucomatous Injury - Tang, Jiahui; Zhuo, Yehong; Li, Yiqing (Frontiers in Cell and Developmental Biology, 2021)
Glaucoma is the most substantial cause of irreversible blinding, which is accompanied by progressive retinal ganglion cell damage. Retinal ganglion cells are energy-intensive neurons that connect the brain and retina, and depend on mitochondrial homeostasis to transduce visual information through the brain. As cofactors that regulate many metabolic signals, iron and zinc have attracted increasing attention in studies on neurons and neurodegenerative diseases. Here, we summarize the research connecting iron, zinc, neuronal mitochondria, and glaucomatous injury, with the aim of updating and expanding the current view of how retinal ganglion cells degenerate in glaucoma, which can reveal novel potential targets for neuroprotection.